2015
DOI: 10.1007/s12032-015-0654-3
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of SRPK1 in TGF-β-induced proliferation and apoptosis in the esophageal squamous cell carcinomas

Abstract: In recent years, transforming growth factor-β (TGF-β) and the serine-arginine protein kinase 1 (SRPK1) have been recommended as a key signal mediator that is involved in oncogenesis. However, the mechanisms underlying TGF-β-SRPK1 pathway-mediated proliferation and apoptosis in the esophageal squamous cell carcinomas (ESCC) have not been well featured till now. We used immunohistochemistry, immunoblotting, and RT-PCR to assess the expression of SRPK1 in 120 cases of ESCC samples and cell lines. Subsequently, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…SRPK1, a highly conserved protein in precursor mRNA translation and splicing, chromatin reconstruction, is dysregulated in different cancers [26, 35]. Moreover, SRPK1 play a critical role in EMT process of human glioblastoma [36].…”
Section: Discussionmentioning
confidence: 99%
“…SRPK1, a highly conserved protein in precursor mRNA translation and splicing, chromatin reconstruction, is dysregulated in different cancers [26, 35]. Moreover, SRPK1 play a critical role in EMT process of human glioblastoma [36].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant SRPK1 expression in either direction can induce constitutive Akt activation and provide a mechanistic basis for previous observations that SRPK1 can be downregulated in some cancer types but upregulated in others (25). Ren et al (26) revealed that SRPK1 mediated TGF-β-induced proliferation and apoptosis by regulating AKT and JNK in ESCC. Thus, the TGF-β-SRPK1 pathway may be a useful target to affect the progression of ESCC.…”
Section: Discussionmentioning
confidence: 60%
“…Liver cancer was also characterized by SRPK1 overexpression, while the latter was correlated with higher stage, larger tumor size, and shorter survival [45][46][47]. In esophageal cancer, high expression of SRPK1 was associated with higher grade, stage, the capacity to metastasize, and shorter overall survival at both univariate and multivariate levels [48].…”
Section: Cancer Type (Primary Location)mentioning
confidence: 98%
“…The SRPK1-induced PI3K/AKT pathway interacts with miR-1296 [45] ↑SRPK1 was found in hepatocellular cancer cell lines [46] ↑SRPK1 was found in hepatocellular cancer cell lines and promoted proliferation ↓SRPK1 suppressed proliferation in vitro and growth in vivo and in vitro SRPK1 interacts with the PI3K/AKT pathway [47] Esophagus ↑SRPK1 was found in esophageal cancer cell lines and promoted proliferation ↓SRPK1 suppressed proliferation, migration, and invasion and enhanced apoptosis in vitro also suppressed tumor growth in vivo SRPK1 interacts with the TGF-β pathways [48] Pancreas ↑SRPK1 was found in pancreatic cancer cell lines ↓SRPK1 suppressed proliferation and enhanced apoptosis and sensitivity to chemotherapy in vitro SRPK1 interacts with SR proteins and regulates apoptosis [22] SRPK1 interacts with the AKT and MAPK pathways [36] Blood (Leukemia) ↓SRPK1 suppressed proliferation in vitro and tumor growth in vivo, while it enhanced cell cycle arrest, apoptosis and prolonged the survival of animal models in MLL-rearranged AML; ↓SRPK1 switched BRD4 splicing, favoring the production of its long isoform SRPK1 modulates the alternative splicing of BRD4, MYB, and MED24 [65] ↑SRPK1 was found in various myeloid and lymphoid leukemia cell lines ↓SRPK1 was cytotoxic and enhanced apoptosis in vitro SRPK1 interacts with the SR proteins and modulates the expression and splicing of MAP2Ks, VEGF, and FAS [66] ↓SRPK1 suppressed proliferation while it enhanced autophagy and apoptosis in a synergistic fashion with chemotherapy in vitro SRPK1 interacts with SR proteins and modulates the expression of MAP2Ks and VEGF and the splicing of RON [67] ↓SRPK1 suppressed proliferation and enhanced apoptosis in vitro in CML SRPK1 interacts with the PARP-caspase-3 pathway [68] Kidney ↑SRPK1 was found in renal cancer cell lines ↓SRPK1 suppressed proliferation, migration, and invasion in vitro, also tumor growth in vivo SRPK1 interacts with PI3K/AKT pathway [50] Brain (Glioma) ↑SRPK1 was found in glioma cell lines ↓SRPK1 suppressed proliferation, migration, and invasion of glioma cells in vitro while it induced resistance to chemotherapy [51] ↓SRPK1 suppressed tumor growth and apoptosis in vivo, also angiogenesis in vitro and in vivo…”
Section: ↓Srpk1 Suppressed Migration and Invasion In Vitromentioning
confidence: 99%
See 1 more Smart Citation